Posisi Muslim dalam Menentukan Pilihan di Pilpres 2019 - Yahya, Yuangga Kurnia (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This study aims to analyze the role and position of individuals in an Islamic society based on al-Qur’an. This research is based on Charles Taylor's individualism theory of a separate person (The Disengaged Self). Interest related to selfhood according to him is an inseparable thing in a community to avoid taqlid, religious fanaticism, and blind nationalism and. Every individuals have to create a disengaged self and strong evaluator themselves.This study indicates that Islamic collectivity has often been distorted into practical collectivism which negates the role of individuals and constructs individuals into forced decisions. Finally, the actions of the community are not based on individual awareness in the community based on al-Qur’an. The freedom self-development will have an impact in buliding an strong Islamic community, and apart from blind fanaticism. Islam is a religion that uplifts human reason to be able to express as freely as possible, even in choosing state leaders.